Kartierung von Starkregenzügen auf Grund ihrer bodenzerstörenden Wirkung - Hartke, Wolfgang (ERDKUNDE, 1954)
In recent years meteorologists have become interested in the paths of clouds, precipitation and gusts. To the geographer a clarification of these problems is important for instance for studies of soil erosion or regional differentiation of the agricultural landscape. This paper deals with attempts to map the strength and course of heavy rains in the Rhine-Main area on the basis of their micro-morphological effects. The examples show that such mapping becomes possible when the rainfall exceeds a certain minimum which differs regionally, and it is even possible in cases where rain gauge data are insufficient to give a clear picture of the actual course of a rainfall path. The further development of this method seems important since, as a result of the comparatively wide mesh of the rain gauge stations, about 50 to 60 per cent, of the heavy rains either escape registration completely or are otherwise registered in an geographically unsatisfactory manner.